In vitro and in vivo ablation of porcine renal tissues using high-intensity focused ultrasound - Damianou, Christakis A. (My University, 2003)
The aim of this paper is to present issues regarding the thermal ablation of porcine renal tissues in vitro and in vivo using high-intensity focused ultrasound (HIFU). Production of lesions in the cortex in vitro is consistent, whereas lesions in the medulla are created whenever there are no air spaces in the medulla. Typically, the lesion length at 2000 W/cm and 5-s pulse duration is around 20 mm and the corresponding width around 3 mm. Lesioning of a large volume was achieved by moving the transducer in a grid formation. Lesioning through a fat layer is possible provided that there are no air spaces between the fat and kidney interface. It was found that, above 3200 W/cm with 5-s pulse duration at 4 MHz, cavitation activity occurred in most of the lesions created. © 2003 World Federation for Ultrasound in Medicine & Biology.
Keywords: Attenuation; Cavitation; Lesion; Simulation; Ultrasound; Cortex; Kidney